Video screen visualization patterns when using a video laryngoscope for tracheal intubation: A systematic review. Issue 1 (6th January 2022) - Dean, Preston; Kerrey, Benjamin
Abstract: Objective: Published studies of video laryngoscopes are often limited by the lack of a clear definition of video laryngoscopy (VL). We performed a systematic review to determine how often published studies of VL report on video screen visualization. Methods: We searched PubMed, EMBASE and Scopus for interventional and observational studies in which a video laryngoscope equipped with a standard geometry blade was used for tracheal intubation. We excluded simulation based studies. Our primary outcome was data on video laryngoscope screen visualization. Secondary outcomes were explicit methodology for screen visualization. Results: We screened 4838 unique studies and included 207 (120 interventional and 87 observational). Only 21 studies (10% of 207) included any data on video screen visualization by the proceduralist, 19 in a yes/no fashion only (ie, screened viewed or not) and 2 with detail beyond whether the screen was viewed or not. In 11 more studies, visualization patterns could be inferred based on screen availability and in 16 more studies, the methods section stated how screen visualization was expected to be performed without reporting data collection on how the proceduralist interacted with the video screen. Risk of bias was high in the majority of included studies. Conclusions: Published studies of VL, including many clinical trials, rarely include data on video screen visualization. Given the nuances of using a video laryngoscope, this is a critical deficiency, which largely prevents us from knowing the treatment effect of using a video laryngoscope in clinical practice. Future studies of VL must address this deficiency.